REKONSTRUKSI SISTEM BIROKRASI PERTANAHAN MENUJU KONSEP KEADILAN DALAM KERANGKA POLITIK HUKUM AGRARIA: TINJAUAN TERHADAP IMPLEMENTASI KETETAPAN MPR RI NO. IX/MPR/2001. - Handoko, Widhi Widhi (Jurnal Konstitusi, 2011)
The use of the impure negative ‘stelsel’ in the land law system in Indonesia might make the bureaucratic system and the public service of the National Land Agency not work well. The system shows many weaknesses and ill-structures. And its main weakness is that the government issues some evidence of ownership in the form of certificate that may function as a formal evidence, where the evidence of land possesion is marked by a land certificate as a absolute evidence. But the government is not responsible for the validity of either physical or juridical data in the certificate. Moreover, the government does not regulate how the National Land Agency should be responsible for issuing the certificate on the rights to the land. The National Land Agency should be designed to support democratization and the establishment of clean and good governance, namely a government that may grow into a rational, transparent government, and that possess a competitive attitude among departments in giving services, that support law enforcement and that is willing to give a public accountability regularly. In reality, the bureaucratic system in the National Land Agency is quasi in nature, since it is characterized by suspense and conflicts among various social structure with various interests based on the operation and exploitation, as a result, the social justice as idealized by the state will not be reached.